Формирователь случайной числовой последовательности с использованием метеорного радиоканала - Репка, М. В. (ХНУРЭ, 2012)
This paper presents a device for the formation of random number sequences using the meteor-burst channel. The device can be used to protect information transmitted by any channel. The block diagram and working principles are presented in this paper.